Buracos negros fantasmas. - Rodrigues, Manuel Eleuterio (2010)
We obtain the general solution of the Einstein-(anti) Maxwell-(anti) Dilaton (EMD)theory for a static, spherically symmetric spacetime in four dimensions. In the phantom(anti) cases, we obtain new solutions with non-degenerate horizon and make the analysis oftheir causal structures. The causal structures of some solutions are exotics, some of themcan not be described in two-dimensional usual Penrose diagrams. We obtain also, usingthe method of Sigma model, new stationary solutions with axial symmetry, for Einstein-anti-Maxwell-Dilaton (E ¯MD) and Einstein-anti-Maxwell-Dilaton-Axion (E ¯MDA) theory.We analyse the causal structure of these new solutions.